Pelatihan Pengembangan Hijauan Pakan di Kelompok Peternak Mekar Desa Merbaun Kecamatan Amarasi Barat Kabupaten Kupang - Gusti Ayu Yudiwati Lestari; Erna Hartati; Gemini Malelak (GOTAVA, 2023)
This training activity aims to introduce the participants to various types of forage that can be used as feed for ruminant livestock, especially cattle. Another objective is to motivate the participants to innovate in feed provision, ultimately encouraging them to start agricultural enterprises, particularly in forage production, to support the development of cattle farming in the Amarasi Barat sub-district of Kupang Regency. The training begins with providing information about different types of forage, planting methods, harvesting age, and post-harvest handling. The methods used to achieve these objectives include counseling, demonstrations, direct practice, mentoring, and evaluation. The training participants are members of the Mekar livestock group in Dusun VI (Puru), Merbaun Village – Kecamatan Amarasi Barat. The results from the mentoring and evaluation activities will be used as a reference for creating future programs related to post-harvest forage technology. After community members have acquired the knowledge and abilities of cattle raising, the community's revenues will provide better outcomes, increase income, and improve welfare in the long run.